Pathophysiology, diagnosis and treatment of somatosensory tinnitus: a scoping review - Haider, Haula; Hoare, Derek J.; Costa, Raquel FP; Potgieter, Iskra; Kikidis, Dimitris; Lapira, Alec; Nikitas, Christos; Caria, Helena; Cunha, Nuno T; Paco, Joao C (Frontiers Media, 2017)
Somatosensory tinnitus is a generally agreed subtype of tinnitus that is associated with activation of the somatosensory, somatomotor, and visual-motor systems. A key characteristic of somatosensory tinnitus is that is modulated by physical contact or movement. Although it seems common, its pathophysiology, assessment and treatment are not well defined. We present a scoping review on the pathophysiology, diagnosis, and treatment of somatosensory tinnitus, and identify priority directions for further research.